PENGARUH PENGELUARAN PEMERINTAH, INVESTASI DAN KONSUMSI RUMAH TANGGA TERHADAP PERTUMBUHAN EKONOMI DI KOTA SURABAYA TAHUN 2011-2018 - Imawan, Bunga Dianty; penagsang, parikesit (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
Economic growth is an important basis in a country or region. Where it can be said to be prosperous if the economic growth in an area increases. Regional Economic Growth is measured by Gross Regional Domestic Product (GRDP). Economic growth of course there are several factors that influence it. This study aims to determine whether Government Expenditure, Investment and Household Consumption have an effect on economic growth. This study uses quantitative research methods. The data processing technique uses multiple linear regression through the SPSS 20 program. The data in this study uses secondary data and data with time series for the period 2011-2018 (8 years). The variables in this study are Economic Growth, Government Expenditure, Investment and Household Consumption. Variable data obtained from BPS (Central Statistics Agency) and dpmptsp (Investment Office) The results of this study indicate that Government Expenditures and Investments have a positive and insignificant effect on Economic Growth, Household Consumption has a positive and significant effect on Economic Growth. Meanwhile, together the variables of Government Expenditure, Investment and Household Consumption have an effect on Economic Growth in the City of Surabaya in 2011-2018